A comprehensive review of the selection of natural and synthetic antioxidants to enhance the oxidative stability of biodiesel. (July 2021) - Jemima Romola, C.V.; Meganaharshini, M.; Rigby, S.P.; Ganesh Moorthy, I.; Shyam Kumar, R.; Karthikumar, Sankar
Abstract: Achievement of sustainable development goals emphasizes alternative fuel strategies posing biodiesel production from plant and animal matter stressing long-chain fatty acid esters. Biodiesel production from renewable energy sources are largely preferred owing to its environment friendly and cost effective economic benefits. Nevertheless several limitations hurdle the efficiency of harnessing the maximal usage render the complexities to be rectified for advancing efficacy of biodiesel. Major issue posing severe hazard can be attributed to the ageing process namely oxidation that positively influence the engine performance and negatively alters storage capabilities. Chemical reactions after iterative chain modifications result in free radicals accumulation ameliorating ease of use in biodiesel. Hence, oxidative stability remains the prominent mechanism for enhancing the compatibility of biodiesel employing suitable antioxidants either natural or synthetic for optimally arresting the chain reactions thereby abating culmination of free radicals. The aim of this review was to analyze and compare the crucial role of natural and synthetic antioxidants in preventing the ageing process of biodiesel. Comparative analysis of the antioxidants that significantly escalates oxidative stability of biodiesel over the last two decades are assessed along with the strategic methodology are scrutinized for apprehending biodiesel stability subsequently based on oxidative stability. Highlights: PCA analysis is performed for the consolidated data of different types of natural and synthetic antioxidants. Various potential oxidative stability testing methods and their procedures are briefly reviewed. Addition of natural antioxidants to biodiesel with 80% of unsaturated fatty acid, suitably increases the induction period. Antioxidants with alkyl or alkoxyl groups at the ortho or para position of the aromatic ring enhance the stability.